2000
DOI: 10.1016/s0167-0115(00)00144-0
|View full text |Cite
|
Sign up to set email alerts
|

Leptin effects on pulsatile gonadotropin releasing hormone secretion from the adult rat hypothalamus and interaction with cocaine and amphetamine regulated transcript peptide and neuropeptide Y

Abstract: Leptin may act as a negative feedback signal to the hypothalamic control of appetite through suppression of neuropeptide Y (NPY) secretion and stimulation of cocaine and amphetamine regulated transcript (CART). We aimed at studying the effects of leptin, CART and NPY on the hypothalamic control of the pituitary-gonadal system. Pulsatile gonadotropin-releasing hormone (GnRH) secretion was studied in vitro using retrochiasmatic hypothalamic explants from adult rats. In the female, GnRH pulse amplitude was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 52 publications
7
58
0
4
Order By: Relevance
“…However, a number of peptidergic cell phenotypes in more caudal areas of the hypothalamus do colocalise leptin receptors, for example NPY/agoutirelated peptide (AgRP) and pro-opiomelanocortin (POMC)/CART neurons in the arcuate nucleus, and melanin concentrating hormone (MCH) and orexin neurons in the lateral hypothalamus (Hakansson et al 1988, Iqbal et al 2001b. Moreover, leptin clearly regulates the activity of multiple hypothalamic peptidergic systems implicated in the control of energy metabolism (for example MCH, NPY, CART, orexin), many of which have been shown to extend rostral projections to areas implicated in the control of GnRH secretion (Parent et al 2000). Given the profound hypogonadotrophism seen when GPR54 receptor signalling is dysfunctional (Seminara et al 2003), an intriguing possibility is that direct metabolic regulation of the GnRH secretory system is via GPR54 receptors known to be expressed in GnRH neurons (Messager et al 2005).…”
Section: The Timing Of Pubertymentioning
confidence: 99%
“…However, a number of peptidergic cell phenotypes in more caudal areas of the hypothalamus do colocalise leptin receptors, for example NPY/agoutirelated peptide (AgRP) and pro-opiomelanocortin (POMC)/CART neurons in the arcuate nucleus, and melanin concentrating hormone (MCH) and orexin neurons in the lateral hypothalamus (Hakansson et al 1988, Iqbal et al 2001b. Moreover, leptin clearly regulates the activity of multiple hypothalamic peptidergic systems implicated in the control of energy metabolism (for example MCH, NPY, CART, orexin), many of which have been shown to extend rostral projections to areas implicated in the control of GnRH secretion (Parent et al 2000). Given the profound hypogonadotrophism seen when GPR54 receptor signalling is dysfunctional (Seminara et al 2003), an intriguing possibility is that direct metabolic regulation of the GnRH secretory system is via GPR54 receptors known to be expressed in GnRH neurons (Messager et al 2005).…”
Section: The Timing Of Pubertymentioning
confidence: 99%
“…6 E) Experiments using in vitro preparations or intracerebroventricular injections have shown that various neurotransmitters can regulate gonadotropin release [38][39][40]. One such neurotransmitters is the cocaine-and amphetamine-regulated transcript (CART) peptide, which has been shown to increase the GnRH pulse amplitude in cycling female rats and to decrease GnRH pulse intervals in prepubertal rats [41][42][43]. These effects can be achieved through direct CART innervation of the GnRH neurons [39,40].…”
Section: Nei Innervation Of Gnrh Neuronsmentioning
confidence: 99%
“…Ароматазная актив-ность обнаружена в клетках околожировой соеди-нительно-сосудистой стромы и может отличаться в различных местах отложения жировой ткани [62]. Различий в уровнях андрогенов у пациентов с «простым» ожирением по сравнению с контроль-ной группой отмечено не было [72] в отличие от повышенной концентрации андростендиона, эс-трона и инсулина у женщин с центральным типом ожирения [64]. У женщин количество андростен-диона, превращаемого в эстрон, зависит от общей массы тела в процентным отношением по следую-щей схеме: 49-63 кг (1%), 63,1-91 кг (1,5%) и > 91 кг (2,3%) [62].…”
Section: адипоцит как эндокринная клеткаunclassified